2021
DOI: 10.51329/mehdioptometry130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual aids for improving reading performance in children with dyslexia

Abstract: Background: Dyslexia is a key learning disorder associated with reading difficulties in children. The purpose of this study was to determine the effectiveness of simple visual devices in improving the reading performance of children with dyslexia. Methods: A case?control study was conducted by selecting 80 school children with dyslexia, aged 8?11 years, from the Special Dyslexic School Program of the Ministry of Education (MOE) Malaysia. Subjects were randomly assigned to four groups: the typoscope, magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The findings of the Barton Intervention Program showed significantly improved reading fluency of students with dyslexia [ 23 ], similar to the findings of the present study. The previous study supported that the reading performance can be improved using aids such as VTM for school children with dyslexia [ 12 ]. Observation and focus group discussions with teachers and children with dyslexia can provide a better understanding of the outcome of the VTM intervention.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…The findings of the Barton Intervention Program showed significantly improved reading fluency of students with dyslexia [ 23 ], similar to the findings of the present study. The previous study supported that the reading performance can be improved using aids such as VTM for school children with dyslexia [ 12 ]. Observation and focus group discussions with teachers and children with dyslexia can provide a better understanding of the outcome of the VTM intervention.…”
Section: Discussionmentioning
confidence: 65%
“…Although VTM has been indicated as the simplest method of both assessing and treating dyslexia [24,25], other than a previous [12] and the present studies, to the best of our knowledge, no study has investigated the efficacy or sustainability of this optical intervention in improving the reading performance of children with dyslexia. Both studies revealed positive effects of the optical intervention using VTM [12]. This positive effect was sustainable despite discontinuation of the intervention at or before 3 months.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations